2018
DOI: 10.1016/j.micpath.2018.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mechanisms of cinnamon and its constituents: A review

Abstract: This review describes the antibacterial effects of cinnamon and its constituents, such as cinnamaldehyde and cinnamic acid, against pathogenic Gram-positive and Gram-negative bacteria. The review also provides an overview of the current knowledge of the primary modes of action of these compounds as well as the synergistic interactions between cinnamon or its constituents with known antibacterial agents. This information will be useful in improving the effectiveness of therapeutics based on these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
233
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(247 citation statements)
references
References 83 publications
5
233
0
9
Order By: Relevance
“…The MIC (0.313) was the lowest compared to other studies in this proper field (de Oliveira et al, ; Ribeiro‐Santos et al, ). Last, the effect of cinnamon EO on bacterial species was gram‐independent in this study, despite the known selective effect of EOs (Vasconcelos, Croda, & Simionatto, ), but in coherence with previous studies showing the efficiency of this EO against both gram positive and gram negative bacteria of both medical and food‐interest microorganisms (Ribeiro‐Santos et al, ). Even though the mode of action of cinnamon EO is still not clear, and might be different against species, a common decrease in intracellular adenosine triphosphate as well as potassium ion (Nowotarska et al, ).…”
Section: Resultssupporting
confidence: 89%
“…The MIC (0.313) was the lowest compared to other studies in this proper field (de Oliveira et al, ; Ribeiro‐Santos et al, ). Last, the effect of cinnamon EO on bacterial species was gram‐independent in this study, despite the known selective effect of EOs (Vasconcelos, Croda, & Simionatto, ), but in coherence with previous studies showing the efficiency of this EO against both gram positive and gram negative bacteria of both medical and food‐interest microorganisms (Ribeiro‐Santos et al, ). Even though the mode of action of cinnamon EO is still not clear, and might be different against species, a common decrease in intracellular adenosine triphosphate as well as potassium ion (Nowotarska et al, ).…”
Section: Resultssupporting
confidence: 89%
“…These results indicated that the tested two phenolic compounds had destructive effects on the cell surface and could alter the external structures of the target bacteria. This may lead to the breakage of cell membrane, and then result in the leakage of proteins, DNA and RNA (Vasconcelos et al ., ). Similar SEM observations were already made in A. acidoterrestris cells treated with grape seed extract, which mainly contained phenolic compounds of catechin and epicatechin (Molva & Baysal, ).…”
Section: Resultsmentioning
confidence: 97%
“…Cinnamaldehyde could cause the impairment of the membrane‐embedded proteins functionality, thereby modifying the cell membrane permeability of the microorganism (Dong et al., ). In brief, the alteration of membrane permeability and the loss of functional proteins transporting molecules or ions disorder the normal physiological metabolism of microbial cells (Vasconcelos, Croda, & Simionatto, ). As Zhang reported, the addition of cinnamon essential oil could effectively inhibit bacterial growth and extend the shelf life of vacuum‐packaged common carp fillets (Zhang et al., ).…”
Section: Resultsmentioning
confidence: 99%